Six year follow-up of students who participated in a school-based physical activity intervention: a longitudinal cohort study - Brooks Lyndon O; Morgan Philip J; van Beurden Eric; Barnett Lisa M; Zask Avigdor; Beard John R (BMC, 2009)
Abstract Background The purpose of this paper was to evaluate the long-term impact of a childhood motor skill intervention on adolescent motor skills and physical activity. Methods In 2006, we undertook a follow-up of motor skill proficiency (catch, kick, throw, vertical jump, side gallop) and physical activity in adolescents who had participated in a one-year primary school intervention Move It Groove It (MIGI) in 2000. Logistic regression models were analysed for each skill to determine whether the probability of children in the intervention group achieving mastery or near mastery was either maintained or had increased in subsequent years, relative to controls. In these models the main predictor variable was intervention status, with adjustment for gender, grade, and skill level in 2000. A general linear model, controlling for gender and grade, examined whether former intervention students spent more time in moderate-to-vigorous physical activity at follow-up than control students. Results Half (52%, n = 481) of the 928 MIGI participants were located in 28 schools, with 276 (57%) assessed. 52% were female, 58% in Grade 10, 40% in Grade 11 and 54% were former intervention students. At follow-up, intervention students had improved their catch ability relative to controls and were five times more likely to be able to catch: ORcatch = 5.51, CI (1.95 - 15.55), but had lost their advantage in the throw and kick: ORthrow = .43, CI (.23 - .82), ORkick = .39, CI (.20 - .78). For the other skills, intervention students appeared to maintain their advantage: ORjump = 1.14, CI (.56 - 2.34), ORgallop = 1.24, CI (.55 - 2.79). Intervention students were no more active at follow-up. Conclusion Six years after the 12-month MIGI intervention, whilst intervention students had increased their advantage relative to controls in one skill, and appeared to maintain their advantage in two, they lost their advantage in two skills and were no more active than controls at follow up. More longitudinal research is needed to explore whether gains in motor skill proficiency in children can be sustained and to determine the intervention characteristics that translate to subsequent physical activity.